The effectiveness of yogic breathing to comfort level of first trimester pregnant mothers at community health center of Kragilan district working area, Serang, Banten, Indonesia - Musfirowati, Fifi; Fahrudin, Adi; Nursanti, Irna (International Journal of Research in Medical Sciences, 2017)
Background: Pregnancy is a natural and physiological process. During the process, women will get some physiological, psychological, and social changes which cause discomfort. Techniques of yogic breathing are able to control respiration and mind. The mechanism of physical change is started by conscious relaxation which happens systematically in the body, which then leads into a deeper relaxation. The study intends to examine the effectiveness of yogic breathing to comfort level of pregnant mothers in first trimester. Methods: The study is a quantitative research with quasi experimental design. It employs pre-test and post-test without control group. The samples are 42 pregnant mothers who were selected by purposive sampling technique which is a type of non-probability sampling. The instrument for measuring comfort level was adopted from GCQ (General Comfort Questionnaire). For the analysis of statistical data, McNemar Test is used. Results: The univariate analysis shows proportional data of respondents’ comfort level frequency before the intervention of yogic breathing was given. Most of the respondents (64.3%) were in discomfort category level of their first trimester pregnancy. Meanwhile, the comfort level after getting yogic breathing intervention is increased. Most of the respondents (66.7%) are in comfort level toward their first trimester pregnancy. From bivariate analysis, the researchers obtained difference in the comfort level proportion of first trimester pregnant mothers before and after getting yogic breathing intervention, with p value 0.007. Conclusions: The study suggests that yogic breathing should be continued as an applied intervention in nursing service especially for pregnant mothers who get discomfort within first trimester.